Meningkatkan Kemampuan Berpikir Kritis Anak Melalui Kegiatan Musical Water Glasses Experiment - Risa Tsani Astari (Universitas Muhammadiyah Gresik, 2024)
This research aims to improve children's critical thinking skills through the musical water glasses experiment activity. This musical water glasses experiment is a learning activity that contains STEAM elements. This research uses the Classroom Action Research method, which is implemented through four repeated stages, namely planning, implementing, observing, and reflecting. The research subjects studied were 14 students from group B RA Al-Irsyad, Soreang, Bandung. Based on the results of data analysis, the critical thinking ability of children in group B RA Al-Irsyad, Soreang, Bandung before the musical water glasses experiment activity was implemented, obtained an average score of 34% which categorised as starting to develop. After implementing the musical water glasses experiment activity, children's critical thinking abilities in cycle I obtained an average score of 58%, which categorised as developing as expected and in cycle II it increased to 83.5%, which shows the category of developing very well. Thus, the musical water glasses experiment activity was proven to be able to improve the critical thinking skills of group B children at RA Al-Irsyad, Soreang, Bandung.